Modeling of autophagy-related gene expression dynamics during long term fasting in European eel (Anguilla anguilla). Issue 1 (December 2017) - Bolliet, Valérie; Labonne, Jacques; Olazcuaga, Laure; Panserat, Stéphane; Seiliez, Iban
Abstract Autophagy is an evolutionary conserved cellular self-degradation process considered as a major energy mobilizing system in eukaryotes. It has long been considered as a post-translationally regulated event, and the importance of transcriptional regulation of autophagy-related genes (atg ) for somatic maintenance and homeostasis during long period of stress emerged only recently. In this regard, large changes inatg transcription have been documented in several species under diverse types of prolonged catabolic situations. However, the available data primarily concernatg mRNA levels at specific times and fail to capture the dynamic relationship between transcript production over time and integrated phenotypes. Here, we present the development of a statistical model describing the dynamics of expression of severalatg and lysosomal genes in European glass eel (Anguilla anguilla ) during long-term fasting at two temperatures (9 °C and 12 °C) and make use of this model to infer the effect of transcripts dynamics on an integrated phenotype – here weight loss. Our analysis shows long-term non-random fluctuatingatg expression dynamics and reveals for the first time a significant contribution ofatg transcripts production over time to weight loss. The proposed approach thus offers a new perspective on the long-term transcriptional control of autophagy and its physiological role.